The Influence of Understanding Tax Regulations, Taxpayer Awareness, and Digitalization of Tax Services on Individual Taxpayer Compliance - Kahar, Aulia Dianty; Nursyirwan, Vivi Iswanti (Universitas Pamulang, 2026)
Respondents in this research were accounting students majoring in taxation at the Faculty of Economics and Business, Pamulang University. They were selected because they have received formal education related to taxation and are considered to possess adequate foundational knowledge to understand tax obligations. Primary data were collected using a structured questionnaire distributed to participants who met the sampling criteria. The purposive sampling technique was applied, resulting in a total sample size of 237 respondents. The variables used in this study consist of Understanding of Tax Regulations (X1), Taxpayer Awareness (X2), and Digitalization of Tax Services (X3) as independent variables, while Individual Taxpayer Compliance (Y) serves as the dependent variable. Before conducting hypothesis testing, the research instrument underwent validity and reliability assessments to ensure that all indicators were appropriate and consistent. The results confirmed that the instrument met the required standards, indicating that it was suitable for further analysis. The findings of this study show that Understanding of Tax Regulations has a positive and significant effect on Individual Taxpayer Compliance. This suggests that individuals with better knowledge of tax rules are more capable of fulfilling their obligations correctly. Taxpayer Awareness also demonstrates a positive and significant influence, indicating that individuals who understand the importance of taxes tend to comply more willingly. Furthermore, the Digitalization of Tax Services contributes positively by simplifying administrative processes and increasing accessibility. Overall, all three variables significantly enhance taxpayer compliance.